Morals Coaching Through Tahfizh al-Quran in Islamic Junior High School: A Case Study in PERSIS Islamic Boarding School in Karangpawitan Garut West Jawa - Laena zakiyah (UIN Sunan Gunung Djati Bandung, 2016)
Porn video cases involved to Islamic junior high school and college students which are the umpteenth of juvenile delinquency in any cases. The above case is certainly influenced by any cases that very concern and also shows the loss of moral education in the education world. The Ministry of Religion and the Ministry of National Education have essentially concerned to improving educational system in Indonesia. It is to lead the formation of moral and religious spiritual that is still seemed very minimal. The aim of this study is to answer the question on what is the expected of learning moral in the purposive line of educational activities through the development of student personality. This paper requires a new concept in reconstructing the concept of formal education today to lead the formation of character or morals, and its implication to the improvement of spiritual-religious values among the students. In the case of MTs Karangpawitan Garut, Islamic Union is seeking to maximize the interaction between cognitive and psychomotor aspects in the whole of education process. Unfortunately, much of them are still trying to internalize the values of the Qur'an as God's revelation to be applied in behavior or morals. Based on the background, this study shows that morals coaching through tahfizh al-quran in Islamic Junior High School can be seen one of the learning model to rebuilding the student character.